Lojistik yönetiminde taşıma sistemleri ve bir model önerisi - Koçak, Habib (My University, 2003)
In views of today's economic conditions, the competition between the firms has been increasing day after day. To stand against this, they begin to search new activities in their business agreement. In addition to this, customer orders have been changing. They want high quality, low cost and just in time response. These exchange make administrators, to modify their business agreement as a logistical management. Specifically, logistics management can be defined as the management of the movement and storage activities performed by the firm. Every firm, manufacturing or service, must effectively manage movement and storage activities to support production and to provide adequate levels of customer service. This impletation address the integration of purchasing for a propane gas supply chain. The focus is on the wholesale side of the supply network. The objective in the purshasing/ routing problem is to minimize the combined costs of purchasing and transportation. Günümüzde ekonomik koşullar nedeniyle, işletmeler arası rekabet artmış ve bu rekabete karşı koyabilmek için, işletmeler çeşitli çalışmalar içine girmiştir. Küresel hale gelen pazardaki müşterilerin istekleri de daha kaliteli, düşük maliyetli ürünler üretilerek ve isteklerine zamanında cevap verilerek giderilmeye başlanmıştır. İşletmeler geleneksel yönetim şeklini, lojistik yönetim anlayışıyla değiştirmiştir. Özellikle lojistik yönetimi, şirket tarafından gerçekleştirilen hareket ve saklama faaliyetlerinin yönetimi olarak tanımlanabilir. Üretim ya da hizmet sektörü içindeki her işletme, üretimi desteklemek ve müşteriye uygun seviyede hizmet sağlamak için, hareketi ve saklamayı etkili biçimde yönetebilmelidir. Uygulamada lojistik faaliyetlerinden taşıma sistemleri üzerinde durulmuştur. Uygulamada bir gaz dağıtım modeli doğrusal olmayan programlama modeli ile çözülmüştür.
Keywords: Taşıma Sistemleri